2022
DOI: 10.1007/s11625-022-01244-6
|View full text |Cite
|
Sign up to set email alerts
|

Development towards low carbon and sustainable agriculture in Finland is possible with moderate changes in land use and diets

Abstract: Food security under climate change, several sustainability problems, and ambitious climate targets are considered challenges for agriculture and food sectors in many countries. Since agricultural production and its land use produce appr. 20% of greenhouse gas (GHG) emissions of Finland, reducing agricultural GHG emissions is important for meeting national target of climate neutrality by 2035. Healthier food diets, maintenance of biodiversity, and reduced nutrient leaching from agriculture are also required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The findings revealed that H8 was supported, with crop output prices exhibiting a strong positive association with profit levels. This aligns with research across cereals [66], horticulture [67], and floriculture [68], where favorable pricing supports farm financial viability. However, smallholders in Uzbekistan often lack market linkages to receive premium values.…”
Section: Findings and Discussionsupporting
confidence: 68%
“…The findings revealed that H8 was supported, with crop output prices exhibiting a strong positive association with profit levels. This aligns with research across cereals [66], horticulture [67], and floriculture [68], where favorable pricing supports farm financial viability. However, smallholders in Uzbekistan often lack market linkages to receive premium values.…”
Section: Findings and Discussionsupporting
confidence: 68%
“…Such activities are in line with the directions of the European Green Deal and will certainly translate into reduced energy consumption and a lower carbon footprint [9,73]. Authors [74] suggest that moderate changes in food diets and land use in Finland can reduce GHG emissions from agriculture by more than 40% by 2050. In the period 2021-2030, the collective target of EU Member States is to reduce greenhouse gas emissions by 30% from the 2005 level by 2030 [5].…”
Section: The Impact Of Land Consolidation On Energy Efficiencymentioning
confidence: 87%
“…The experience of village cadres, agricultural income, degree of organization, business scale, and knowledge of fertilization technology are positively and significantly correlated with farmers adoption behaviors (Hou et al, 2019). The reduction in demand for meat and the cultivation of feed crops will reduce greenhouse gas emissions and release land for carbon sequestration through afforestation (Heikki and Janne, 2022).…”
Section: Factors Influencing the Development Of Low-carbon Agriculturementioning
confidence: 99%